Ontology−Based Classification of Molecules: a Logic Programming Approach - Magka, D (2012)
We describe a prototype that performs structure-based classification of molecular structures. The software we present implements a sound and complete reasoning procedure of a formalism that extends logic programming and builds upon the DLV deductive databases system. We capture a wide range of chemical classes that are not expressible with OWL-based formalisms such as cyclic molecules, saturated molecules and alkanes. In terms of performance, a noticeable improvement is observed in comparison with previous approaches. Our evaluation has discovered subsumptions that are missing from the the manually curated ChEBI ontology as well as discrepancies with respect to existing subclass relations. We illustrate thus the potential of an ontology language which is suitable for the Life Sciences domain and exhibits an encouraging balance between expressive power and practical feasibility.